(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper investigates the relationship between Industry 4.0 technologies and the competitiveness of manufacturing enterprises. Industry 4.0, which integrates digital technologies such as artificial intelligence, big data, robotics, and the Internet of Things, is transforming production processes and business models, fostering innovation, and enhancing global competitiveness. The study aims to explore how these technologies influence manufacturing efficiency, flexibility, and product quality, and to identify the main motivations and barriers faced by companies in adopting Industry 4.0 technologies. The research employs several methodologies: systematic literature review - to summarize existing research on Industry 4.0 and its impact on competitiveness, identifying key innovations and trends in manufacturing; bibliometric analysis - analysing scientific publications to map the research landscape, identify influential works, and discern key technological trends in Industry 4.0; survey method - a survey of 100 Ukrainian manufacturing enterprises was conducted to assess the main motivations and barriers for adopting Industry 4.0 technologies. The results show that Industry 4.0 allows companies to significantly improve productivity, reduce costs and adapt to changing market conditions. However, the introduction of new technologies is accompanied by a number of risks, including economic, technical problems, including high initial investments, cyber security, and the need for new skills of employees. The challenges associated with the introduction of these technologies, including financial, technical and organisational costs, as well as problems associated with resistance to change, are considered. The reasons for this resistance are analysed, including personal interests of employees, distrust and uncertainty. Effective methods of managing resistance to change, such as communication, training and active participation of employees in the change process, are proposed. The importance of clear communication, support and skills development for successful technology adoption is emphasised..